The Theory and Practice of International Criminal Law : Essays in Honor of M. Cherif Bassiouni - Sadat, Leila Nadya; Scharf, Michael P., 1963- (Martinus Nijhoff Publishers, 2008)
A collection of essays about the theory and practice of modern international criminal law, with a focus on Cherif Bassiouni's unique legacy within this area.